Knowledge and Attitude of Students Toward Sex Education in Secondary School Students in Katsina Zonal Education Quality Assurance of Katsina State, Nigeria - Agada Adah Abechi; Ruth David Damboama; Arinde Kazeem Ajiboye (Researchparks Publishing, 2024)
This study was designed to investigate the knowledge and attitudes of students toward sex education in secondary schools in Katsina Zonal Education Quality Assurance, Katsina State, Nigeria. The desire to embark on this study was borne out of the realization from observation of the researchers that teachers may be facing a number of stress factors due to the demanding nature of their career. Appropriate research questions and hypotheses were raised to guide this study towards achieving the stated objectives. The descriptive survey research method was used. A total of one thousand, two hundred and twenty-one (1221) questionnaire were administered in nine secondary schools in Katsina Zonal Education Quality Assurance of Katsina State, Nigeria. A pilot test was conducted to determine the reliability of the instrument using the split-half method of reliability with the reliability index of 0.05. The questionnaire was administered by the researcher with the support of two research assistants. Frequency counts, percentage, means scores, t-test statistical techniques were employed in the data analysis. At the end of the analysis, the findings showed that students have positive attitude towards the knowledge of sex education. The attitude of adolescent differ toward the introduction of sex education in secondary schools on the basis of gender of the respondents. There is a significant difference in the attitude of male and female adolescents towards the introduction of sex education in schools. It is therefore recommended among others that the knowledge of sex education should be included into the school curriculum and the need for comprehensive counseling programmes in secondary schools.